Photoassociation of rotating ultra-long range Rydberg molecules - Thomas, O.; Lippe, C.; Eichert, T.; Ott, Herwig (Journal of Physics B: Atomic, Molecular and Optical Physics, 2018)
We discuss the rotational structure of ultra-long range Rydberg molecules and their angular nuclear wave function. Expressing the complete molecular wave function in a laboratory fixed frame, we derive the transition matrix elements for the photoassociation of free ground state atoms. The coupling strength depends on the angular momentum coupling in the Rydberg molecule, which differs for the various types of Rydberg molecules. This work explains the different steps to calculate the wave functions and the transition matrix elements in a way, that they can be transferred to other Rydberg molecules involving different atomic species or molecular coupling cases.
CRIS-Team Scopus Importer:2023-03-27
Keywords: photoassociation; rotational spectra; Rydberg molecules